Language proficiency and the speech act of complaint of Chinese EFL learners - Li, Rui; Raja Rozina Raja Suleiman, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Complaint is an under-researched speech act in the field of interlanguage pragmatics. Making a complaint runs the risk of impairing the relationship between speaker and hearer as it requires the speaker to express displeasure and frustration to what is believed to be the responsibility of the hearer. The speaker, therefore, has to use appropriate linguistic forms bearing in mind social conventions to make the hearer take some action of repair or to avoid interactional conflicts. For L2 learners, making complaints in a second/foreign language is more difficult as they may lack both sociocultural and L2 knowledge. This study investigated the ability of Chinese EFL learners to produce complaints and its relationship with their L2 proficiency. Thirty-two Chinese university students and five native speakers of American English completed a Free Discourse Completion Test (FDCT); English proficiency was measured by learners’ performance in TEM-4. Data elicited from the FDCT were analysed using a holistic rating scale for the overall appropriateness of complaints and a coding framework for complaint strategies and modifications. Results showed that learners were unable to produce appropriate complaints and L2 proficiency significantly influenced the overall appropriateness of complaints. Differences were also identified in strategies and external and internal modifications used by learners of different proficiency levels. The study suggested that the production of complaints by Chinese learners is greatly influenced by their native culture. In addition to improving L2 proficiency, lessons on cultural differences should be introduced for them to improve the ability to complain in English.